Contemporary art in the Federal Republic of Germany : 12 collections of 30 graphics : Art centres Berlin (West) - Hamburg. - Adriani, Götz (Stuttgart : IFA - Institut für Auslandsbeziehungen Stuttgart, 1978)
Ackermann, Peter ; Albert, Hermann ; Asmus, Dieter ; Baumgarten, Bodo ; Brehmer, Klaus-Peter ; Duwe, Harald ; Grützke, Johannes ; Hödicke, Karl Horst ; Janssen, Horst ; Köthe, Fritz ; Mavignier, Almir ; Nagel, Peter ; Nöfer, Werner ; Schmettau, Joachim ; Schoenholtz, Michael ; Sorge, Peter ; Störtenbecker, Nikolaus ; Vostell, Wolf ; Walther, Franz Erhard ; Winner, Gerd ; Wunderlich, Paul
Biog. [1 p.]
12 collections of 30 graphics. Each will provide a survey of contemporary graphic art in the Federal Republic of Germany in a sequence of exhibitions appearing at regular intervals. They are entitled "Tournee-Ring". (...) Planned and selected in 1974 by Dr. Götz Adriani, (...) Dr. Wulf Herzogenrath (...) Organized by the Institute for Foreign Cultural Relations
Engels
boek
Keywords: Duitsland; Berlijn; Hamburg